Penanaman Sifat Integritas dan Gerakan Anti Korupsi Melalui Sosialisasi di SMA Swasta Maha Bodhi Kabupaten Karimun - Handra Dermawan; Helen Helen; Jackson Jackson; Jonathan Jonathan; Tasya Chandra; Winsherly Tan (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
Indonesia is one of the most corrupt countries in Asia. The minimum knowledge about corruption among the citizens has made them get used to the term “corruption”. In the future, the youth generation will lead this country. From the field research on Maha Bodhi High School, students said that they know less about corruption. Therefore, there is an urge for action to improve their knowledge about corruption and instill the value of anti-corruption. Through one of the three corruption eradication strategies, namely Education and Campaigns, anti-corruption values can be instilled as a preventive effort. As one of the forms of Education and Campaigns, socialization can be done with the assistance of online media, Zoom Meeting. The socialization was addressed to students from Maha Bodhi High School in the Province of Riau Islands. The socialization material includes general knowledge about corruption and anti-corruption values that must be instilled in every individual. The socialization went well and participants have high enthusiasm in asking questions related to the material that had been delivered by the speakers. Participants were encouraged to take part in the “Integrity and Anti-Corruption Movement”. Although the socialization is a success, there are several obstacles that occurred, such as bad internet connection and lack of interaction between speakers and participants due to online media. With this socialization, corruption prevention efforts can be done by Maha Bodhi High School students. The expectation from this socialization that has been carried out is that students can become disciplined citizens that actively challenge corruption.